Effect of Sulforaphane on Bladder Compliance in a Rat Model of Partial Bladder Outlet Obstruction. (18th June 2019) - Liu, Chong; Wan, Xiang; Gu, Meng; Chen, Yanbo; Cai, Zhikang; Zhou, Juan; Chen, Qi; Wang, Zhong
Abstract : Aims . To investigate the effect of Nrf2 activator sulforaphane (SFN) on bladder compliance and the underlying mechanisms in a rat model of partial bladder outlet obstruction (BOO). Methods . Male 8-week-old Sprague-Dawley rats were divided into three groups. BOO rats were given daily 0.5 mg/kg sulforaphane (BOO+SFN) or vehicle (BOO) intraperitoneally for 4 weeks, while sham-operated rats were treated with vehicle (Sham). Bladder compliance, histological alteration, and collagen deposition were evaluated. The expression levels of collagen I, collagen III, MMP-1, and TIMP-1 were measured by immunohistochemistry and western blotting. Results . BOO led to a significant decrease in bladder compliance. The change was partially restored by SFN treatment. The expression of MMP-1 was significantly decreased accompanying with increased TIMP-1 expression in BOO rats compared with that in Sham rats, which was ameliorated by SFN treatment. Moreover, the increased collagen I/collagen III ratio in the BOO group was reversed by SFN treatment. Conclusions . Sulforaphane suppressed collagen deposition by regulating the MMP-1 and TIMP-1 expression and decreasing the collagen I/III expression ratio in BOO rats and improved bladder compliance.